Investigation on performance of DC motor in exhaust application using vibration based condition monitoring - Raghavendra Pai K, Lokesh K S, Veeresh R K, Ananthakrishna Somayaji,Nithin Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In allusion to the issue of the preventive maintenance in industry 4.0 a proactive approach on maintenance such as predictive maintenance is gaining more and more scope. This paper provides a brief insight on the basic methodology for analysis of complex vibration signals taken from the machine of interest. In the past several years there have been several developments in the field of condition monitoring however reducing the complexity of the analysis has helped in achieving better results. This paper has proposed a novel and effective method to simplify the use of vibration-based condition monitoring analysis of a motor in a industrial segment. Also using the method of vibration based condition monitoring it was possible to establish the efficacy and efficiency of the given method in a industrial space.